Association Between Self-Efficacy and Aggression Among College Students - Malagonda, Patil Vishwanath; Minchekar, Vikas S. (TAZKIYA: Journal of Psychology, 2021)
Aggressive behavior in sports and group performance is critical in today's scenario. Self-efficacy can play a crucial role in aggressive behavior. Hence, to test this assumption study was undertaken to assess the association between self-efficacy and aggression. It was hypothesized that self-efficacy and aggression are positively and significantly related to each other. This study's sample contained 80 students, and they were recruited from Dr. Ghali College, Gadhinglaj. The sampling technique was non probability sampling in which everyone doesn’t have the same chance for being chosen as a sampling. This study administered self-efficacy measure using the scale by G. P. Mathur and Dr. Raj Kumari Bhatnagar and aggression scale by G. P. Mathur and Dr. Raj Kumari Bhatnagar to 40 male and 40 female college students. Obtained data were analyzed by Student t-test and PPMCC test. Results revealed that there is a significant sex difference in self-efficacy and aggression. Moreover, the association between self-efficacy and aggression among college students was also found significant.